La editio quaestoria en el Bajo Imperio: el ejemplo de Quinto Memio Símaco - Beltran Rizo, Enric; Jiménez Sánchez, Juan Antonio (Gerión. Revista de Historia Antigua, 2005)
The matter of the editio quaestoria in the late Roman Empire still raises many questions nowadays due to the scarcity of sources related. In this study, we wonder about the translation of the date of celebration to october, the high degree of absenteeism (observed in Philocale’s calendar), the collegiality of this magistrature (one may assume that it does not exist as such in the show organization), or the professio quaestoria, which allows to know in advance how many questors would offer games. As an example, we analyze Symmachus’s correspondence referring his son Memmius’s editio, which occurred in 393 AD.